2(d+6)=3(d-1)

Simple and best practice solution for 2(d+6)=3(d-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(d+6)=3(d-1) equation:


Simplifying
2(d + 6) = 3(d + -1)

Reorder the terms:
2(6 + d) = 3(d + -1)
(6 * 2 + d * 2) = 3(d + -1)
(12 + 2d) = 3(d + -1)

Reorder the terms:
12 + 2d = 3(-1 + d)
12 + 2d = (-1 * 3 + d * 3)
12 + 2d = (-3 + 3d)

Solving
12 + 2d = -3 + 3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-3d' to each side of the equation.
12 + 2d + -3d = -3 + 3d + -3d

Combine like terms: 2d + -3d = -1d
12 + -1d = -3 + 3d + -3d

Combine like terms: 3d + -3d = 0
12 + -1d = -3 + 0
12 + -1d = -3

Add '-12' to each side of the equation.
12 + -12 + -1d = -3 + -12

Combine like terms: 12 + -12 = 0
0 + -1d = -3 + -12
-1d = -3 + -12

Combine like terms: -3 + -12 = -15
-1d = -15

Divide each side by '-1'.
d = 15

Simplifying
d = 15

See similar equations:

| 8x-1=2x+6 | | 2n-3=28 | | (x-5.4)+(y-0.6)=9 | | 1.2454x^2+34.9x-19.6=0 | | x^2+x-1=5 | | 4x^2+6x+4=0 | | 8m-26=30 | | 8(4y-3)=72 | | 5x^2-2xy+2y^2-6y=35 | | 82=4(22+1) | | 5ln(x)+3=0 | | 49.3x^2-64x+19.2=0 | | 4x-6y=10solvey | | 4x-6y=10fory | | 3(x-250)=3500 | | 4(6y+9y)=-10 | | 2m+15=8m+69findm | | 15x*2-64y*2= | | log(1-2x)+log(2-x)=1.9 | | 12n=8n+16 | | ln(4x)+ln(5+x)=2 | | 5x+3y=6fory | | 6(2x-1)-2(5x-9)=2 | | 2(3x-1)+2(2x-9)=-2 | | (4^3/4x^2y^3)(4^3/4x^-2y^-5) | | 3(5x-1)=2(7x-9) | | ln(-3x+5)=ln(4x-2) | | 2x-20+3x+x+10=180 | | -3x^3-15x^2+72x= | | 6a-5a+9b+2b= | | 0.4x+-0.2(50+x)=0.2(60) | | 0.4x-0.02(50+x)=0.2(60) |

Equations solver categories